Partitioning behavior and occurrence of airborne polyfluorinated alkyl substances in Singapore - Wu, Yaoxing (2013)
Polyfluorinated alkyl substances (PFASs) are a large group of organic chemicals, many of which are persistent in the environment, bioaccumulative and pose potential adverse effects to human health. The presence of neutral, volatile PFASs in air are of particular concern, as air quality is an important determinant in terms of public health. However, little experimental information is available on the physicochemical properties of volatile PFASs. The short-term concentration variations of airborne PFASs also remain unknown due to the lack of a highly sensitive analytical method which can also achieve satisfying temporal resolution. Therefore, the aim of current work is to improve our understanding of the partitioning behavior, occurrence and source strength of neutral, volatile PFASs in Singapore. Firstly, air–water partition coefficient (KH) of 4 fluorotelomer alcohols (FTOHs), a subgroup of volatile PFASs, was measured using inert gas-stripping method (IGS). KH values of FTOHs showed strong propensity to partition into air. However, the expected linear dependence of KH on molecular weight was not observed. The unique molecular geometry of FTOHs, with hydrogen bonding and molecular contortion, was probably responsible for the unusual phenomenon. The results were compared to predictions made by SPARC and EPI suite. The erroneous predications given by modeling software packages appeared to confirm the unusual behavior of the compounds.Secondly, the study attempted to develop a novel method based upon thermal desorption and GC–MS for determination of indoor airborne volatile PFASs, including four FTOHs, two fluorooctane sulfonamides (FOSAs), and two fluorooctane sulfonamidoethanols (FOSEs) through low-volume active air sampling. The optimization of sorbent combination was also conducted. The method recovery exhibited significant improvement compared with other existing methods such as passive air sampling method. The approach also achieved relatively high temporal resolution and low noise level. It has been successfullyapplied to routine quantitation of targeted PFASs in indoor office environment of Singapore, which provided further insights toward the indoor source strength of PFASs and performance of building air handlings. Thirdly, the developed thermal desorption method was further applied for determination of target PFASs in urban atmosphere through low-volume active air sampling (0.108 m3). It displayed greatly improved method recovery but higher detection limits in comparison with the conventional protocol, which employs highvolume sample collection (450 m3) and solvent-based sample extraction. Comparison of their performances in the real samples of urban atmosphere showed a higher portability and temporal resolution of thermal desorption method, which would be very useful in source apportionment analysis and assessment of concentration variations in highly-urbanized regions. In addition, the concentration levels of PFASs detected in the ambient air of Singapore were more in line with the European pattern and might indicate an increasing tendency toward using FTOHs in these regions.